Cytogenetics and comorbidity predict outcomes in older myelodysplastic syndrome patients after allogeneic stem cell transplantation using reduced intensity conditioning. Issue 14 (21st March 2017) - Yucel, Orhan Kemal; Saliba, Rima M.; Rondon, Gabriella; Ahmed, Sairah; Alousi, Amin; Bashir, Qaiser; Ciurea, Stefan O.; Popat, Uday; Khouri, Isa; Marin, David; Rezvani, Katy; Kebriaei, Partow; et al.
Abstract : BACKGROUND: Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is the only treatment with a curative potential for myelodysplastic syndrome (MDS) patients. Allo‐HSCT has substantial risks, particularly in the elderly, and its role for older MDS patients has yet to be defined. METHODS: We analyzed 88 MDS patients aged ≥ 60 years with allo‐HSCT after reduced intensity conditioning regimens over the last decade. The study cohort had high risk features; 47 of 88 (53.4%) patients were > 65 years of age, 24 (27%) patients had cytogenetic abnormalities consistent with monosomal karyotype (MKpos), 33 (38%) patients had histological subtype of RAEB‐1 and RAEB‐2 at diagnosis, and 45 (51%) patients had a hematopoietic cell transplantation–comorbidity index (HCT‐CI) of ≥ 3. RESULTS: The 3‐year incidence of progression, transplant‐related mortality (TRM), and overall survival (OS) were 26% (95% confidence interval [CI], 18%‐37%), 35% (95% CI, 26%‐47%), and 41% (95% CI, 30%‐52%), respectively. MKpos was the only prognostic factor that increased the risk of disease progression compared with good‐risk cytogenetics (hazard ratio [HR] = 9.5, P = .003) as well as MKneg (HR = 3.3, P = .01). For TRM, HCT‐CI ≥ 3, but not age >65 years, was associated with worse outcomes (HR = 3.1, P = .007). Cytogenetics and HCT‐CI enabled us to identify prognostic groups for OS. MKpos patients had the worst 3‐year OS (17%), whereas patients with good‐risk cytogenetics and HCT‐CI < 3 had the best OS (92%). CONCLUSION: Our results confirm that allo‐HSCT can provide long‐term survival in older MDS patients. Cytogenetics and HCT‐CI identify prognostic risk groups and guide selection of older MDS patients who are candidates for allo‐HSCT. Cancer 2017;123:2661‐70 . © 2017 American Cancer Society . Abstract : Outcome data in older myelodysplastic syndrome (MDS) patients with allogeneic stem cell transplantation is limited, hence we investigated the outcomes in this population with the use of reduced intensity conditioning. Survival after hematopoietic stem cell transplantation (HSCT) depends on cytogenetics and hematopoietic cell transplantation–comorbidity index in older MDS patients, and decisions to proceed with HSCT should take these factors into account.